Synthesis and Characterization of Crosslinked b-Cyclodextrin and Their Sorption Capacities Towards Phenol from Wastewater - Zhou, Yu-Qing; Huang, Juan; Han, Ping-Fang; Lv, Xiao-Ping (Asian Journal of Chemistry, 2012)
The crosslinked b-cyclodextrin polymer was produced by crosslinker 2,4-toluene diisocyanate (TDI). The influencing factors and optimum synthesis technological conditions were selected via orthogonal experimental method and product yield. The results suggest that the mole ratio of n (isocyanate): n (b-cyclodextrin) is about 1:9, mass ratio of catalyst (dibutyl tin dilaurate and triethylene diamine) equal to 1:1.5, 2,4-toluene diisocyanate is used as diisocyanate, reaction temperature is 70 ºC and reaction time is 9 h. The polymer was characterized by infrared spectrum (FT-IR), scanning electron microscope and thermogravimetric analysis. The result indicates that the crosslinked b-cyclodextrin-2,4-toluene diisocyanate polymer keeps cavity structure of b-cyclodextrin and forms a network structure. The crosslinking reation generates carbamic acid ester base bond. Technological parameters of removal phenol waste water were optimized by adsorption experiments. Regeneration times and adsorptive capacity were study. Controlling limit phenol wastewater pH was 5-7. The maximum amount of polymers was 40 mg/mL. The adsorption rate and adsorbability were low with the increasing of phenol wastewater initial concentration. Regeneration process of adsorbent soaked by methyl alcohol and washed by deionized water. The adsorption efficiency retained more than 88 % after 10 times regeneration.